Sustainable Architectural Design in Indonesia: Responding the Current Environmental Challenges - Gunawan Tanuwidjaja; Lo Leonardo (RUAS (Review of Urbanism and Architectural Studies), 2011)
The impacts of environmental destructions were felt in Indonesia. The irregular weather patterns, extreme temperatures, as well as floods affected many vulnerable areas in the Country oftentimes. Great numbers of environmental as well as man-related disasters were recorded such as: 12 earthquakes & tsunamis (in 2009), 8 volcanic eruptions (in 2008), 631 floods & landslides (in 2009), and 340 typhoons (in 2009). In total 416 lives were killed and 7,444 houses damaged. And the increasing numbers of environmental disasters was observed. Further, poverty and weal legal enforcement caused deforestation and severe biodiversity loss. All these challenges required real solution with Indonesian Sustainable Architectural Design Framework, not only the “green rating”. And the objective of the research was to find Framework of Sustainable Architectural Design Strategy in Indonesia responding to social economic conditions and addressing these environmental challenges. The framework was urgently needed by Building Construction Sector especially by Indonesian Institute of Architects (IAI). And lastly, it should be sustained with the active participation of all stakeholdersKeywords: Indonesian Sustainable Architectural Design, Environmental Challenges in Indonesia